Sistem Pendukung Keputusan Rekomendasi Pekerjaan Bagi Fresh Graduate Dengan Penggabungan SAW Dan TOPSIS - Rahardhiyan Wahyu Putra; Ulla Delfana Rosiani (P3M Politeknik Negeri Banjarmasin, 2021)
Decision Support System is a system that supports humans to determine something based on mathematical calculations. Decision Support Systems will be made by researchers as a tool that will be used to help fresh graduates to choose jobs according to their interests. The object that will be used is the graduates of the Information Technology Department at the State Polytechnic of Malang. The method used for this system combines the SAW and TOPSIS methods.